1990
DOI: 10.1099/00221287-136-4-713
|View full text |Cite
|
Sign up to set email alerts
|

A breakdown in macromolecular synthesis preceding differentiation in Streptomyces coelicolor A3(2)

Abstract: ~ ~~A transitory cessation of growth was recorded in Sfrepfomyces coelicolor A3(2) at the end of vegetative mycelium formation on solid medium. In the same phase a striking reduction in protein and nucleic acid synthesis was detected. Growth and macromolecular synthesis resumed, nearly reaching the original values, when morphological differentiation occurred. It is concluded that a physiological stress occurs within the bacterial population just before the onset of the morphological differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 3 publications
3
50
0
1
Order By: Relevance
“…Since A-factor did not restore normal mycelium formation, its presence appears not to play a determining role. It is also noteworthy that Granozzi et al (1990) reported a transitory cessation of macromolecular synthesis (particularly of RNA) just before aerial mycelium was formed in S . coelicolor A3(2).…”
Section: Idiscussionmentioning
confidence: 99%
“…Since A-factor did not restore normal mycelium formation, its presence appears not to play a determining role. It is also noteworthy that Granozzi et al (1990) reported a transitory cessation of macromolecular synthesis (particularly of RNA) just before aerial mycelium was formed in S . coelicolor A3(2).…”
Section: Idiscussionmentioning
confidence: 99%
“…These mycelial bacteria follow a complex developmental program that includes two types of interrelated differentiation i.e., (i) a morphological differentiation where aerial hyphae, whose tips ends will differentiate into spores, arise from the substrate (vegetative) mycelium and (ii) a physiological/metabolic differentiation characterized by the production of the so-called secondary metabolites. The onset of both types of differentiation correlates with one of the most sophisticated examples of a programmed cell death (PCD) process in prokaryotes (Granozzi et al 1990;Miguelez et al 1999). The latest model suggests two rounds of PCD during Streptomyces life cycle (Manteca et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The second round of PCD starts when this mycelium produce surfactants-like peptides/proteins necessary for aerial growth (Claessen et al 2006). This round of PCD is thought to correspond to the short period of growth cessation called the transition phase that takes places during the exponential growth and is followed by a slower regain of growth before entry into stationary phase (Granozzi et al 1990;Puglia et al 1995;Manteca et al 2005). The cell death paroxysm at the transition phase causes intensive release of intracellular compounds into the extracellular environment (Manteca et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological differentiation of Streptomyces coelicolor is accompanied by the production of degradation enzymes (Chater, 1989;Granozzi et al, 1990). Various extracellular proteases participate in the assimilation of external proteinaceous nitrogen sources (Shapiro, 1989) and a recent study of the regulation of protease activities during growth and mycelium development of Streptomyces exfoliatus SMF13 showed that the production of Abbreviations: CTP, chymotrypsin-like protease; MTP, metalloprotease; TLP, try psi n-l i ke protease.…”
Section: Introductionmentioning
confidence: 99%